Method to test fungal degradation of bamboo and wood using vermiculite as reservoir for moisture and nutrients - Wei, Dongsheng; Schmidt, Olaf; Liese, Walter (Maderas. Ciencia y Tecnología, 2025)
Proposed is a method to investigate degradation of lignocelluloses by pure cultures of basidiomycetes using preserving jars with vermiculite as reservoir for water and nutrients. Bamboo samples of Gigantochloa atroviolacea and Phyllostachys pubescens and wood samples of Fagus sylvatica and Pinus sylvestris were inoculated with the brown-rot fungus Coniophora puteana and the white-rot fungus Schizophyllum commune. The fungi were cultured on vermiculite containing different amounts of tap water or malt extract solution. Mass loss of the bamboos after 32 weeks was low and did not show a remarkable influence of moisture content and nutrient addition. However, considerable degradation of Pinus sylvestris sapwood occurred by C. puteana whereby moisture and nutrients influenced aggressiveness.